Atomic insight into concurrent He, D, and T sputtering and near-surface implantation of 3C-SiC crystallographic surfaces. (May 2019) - Bringuier, S.; Abrams, T.; Guterl, J.; Vasudevamurthy, G.; Unterberg, E.; Rudakov, D.; Holland, L.
Highlights: Newly developed interatomic potential to treat He and H interactions with 3C-SiC. Si and C physical sputtering yields from 3C-SiC are significantly different. Crystallographic orientation and temperature show limited influence on sputtering yields. He, D, and T implantation profiles and retention depend on crystallographic orientation. Abstract: We present results from atomistic simulations of sputtering and near-surface implantation of concurrent He, D, and T bombardment of cubic silicon carbide (3C-SiC). This is achieved by first establishing a many-body interatomic potential parameter set to treat interactions of He and hydrogenic species in 3C-SiC informed by ab-initio calculations. To obtain sputtering yields we perform both classical molecular dynamics and binary collision approximation simulations for normal incident particles having energies ranging from 25 to 800 eV. We find that due to differences in species surface binding energy of various crystallographic surfaces in 3C-SiC, the sputtering yield of Si is significantly less than that of C, but sputtering yields show limited sensitivity to crystallographic surface orientation. An exception to this occurs when the terminating crystallographic surface plane is more rich in Si rather than C, resulting in comparable sputtering yields of Si and C. The influence of temperature on sputtering is explored and shows limited effect. Finally, the nature of implanted He, D, and T within 3C-SiC surfaces is investigated to understand implantation profiles and stability of defects.